Green Nanoparticles in Sustainable Therapeutics and Future Sustainability: Green Nanoparticles in Sustainable Therapeutics - Kamran, Tasmiya; Rehman, Arsheen; Malik, Aaroj; Siddiqui, Mahrukh; Ahmad, Rehan; Muhammad Islam, Saad; Hurera, Abu; Rehman, Huda; Walait, Manam; Walayt, Salman (Pakistan Journal of Health Sciences, 2023)
Green nanoparticles (GNPs) are being produced from microbial and plant sources and have numerous applications in various fields. The article focuses on the NPs that provide various focal points in the many scientific and technological fields for the cutting-edge uses of nanoparticles. Due to their toxicity, cost-effectiveness, ease of use, and environmental friendliness, green NPs are extremely important. It is closely observed how important green NPs are to the development of science and technology in the context of sustainable therapeutics. The only issue with green nanoparticles is occasionally how toxic they can be. A sustainable future, which the entire world looks forward to, is directly related to green nanoparticles and their role in numerous applications.